Cultural, Morphological and Pathological Characterization of Colletotrichum falcatum Causing Red Rot Disease of Sugarcane in Thailand - Sangdit, Pakamart; Leksomboon, Chalida; Lertsrutaiyotin , Rewat (Agriculture and Natural Resources, 2014)
Fifteen isolates of Colletotrichum falcatum were isolated from sugarcane in five different areas in Thailand. All isolates were identified by polymerase chain reaction (PCR) technique using primers its1 and its4 derived from internal transcribed spacer (ITS) sequences to amplify a unique DNA fragment of 590 bp from C. falcatum. Amplified DNA bands of each isolate were sequenced and determined their identity using the GenBank database. Nucleotide sequence analysis of the ITS sequences indicated that the 15 isolates showed 95.32–100% identity with each other and 96.30–97.74% related to C. falcatum. Variation in the cultural, morphological and pathological characteristics of the 15 isolates were investigated. The 15 isolates were differentiated into two distinct groups (light and dark types) based on the colony color character. Ten isolates (LB1-4, LB1-6, LB1-7, LB2-1, LB2-2, LB2-3, LB2-4, LB2-5, LB2-7 and NM1) in the light type produced white color colonies whereas isolates KB1, KBL1-1, KBL1-2, KBL1-3 and SBL1 in the dark type had gray color colonies. The growth rate among all isolates varied from 11.6 to 12.9 mm.d-1 and was not significantly different. The 15 isolates produced setae and conidia that were hyaline, one-celled, falcate or sickle-shaped. The conidia of all isolates ranged between 21.42 and 28.56 µm in length and from 2.38 to 4.76 µm in width. Appressoria were terminal, rarely intercalary, aseptate and the overall shape was globose or clavate, with edges entire. The appressorial size ranged between 10.68 and 16.02 µm in length and from 8.01 to 13.35 µm in width. Pathogenicity of the 15 isolates on stalks of sugarcane varieties E-Heaw, K84-200, K88-92 and K93-236 by the plug method was used to characterize the pathogenic variability among the isolates of C. falcatum. Nine isolates (LB1-4, LB1-6, LB1-7, LB2-1, LB2-2, LB2-3, LB2-4, LB2-5, LB2-7) from localities affected with the red stalk rot epidemic possessed a degree of pathogenicity toward the susceptible varieties E-Heaw and K93-236, while those from localities without the red stalk rot epidemic (NM1, KB1, KBL1-1, KBL1-2, KBL1-3, SBL1) were nonpathogenic on both varieties. None of the isolates produced the typical red rot symptom on stalks of the resistant varieties K84-200 and K88-92. A principal finding in this study was that only C. falcatum samples originating from localities affected with the red stalk rot were capable of infecting stalks of sugarcane and they had a light type of colony character. The results presented in the pathogenicity test demonstrated that C. falcatum causing red rot disease of sugarcane in Thailand may be differentiated into two distinct races (pathogenic and nonpathogenic) based on their pathological character on the stalks of sugarcane.